Case report: Congenital short bowel syndrome - Palle, Lalitha; Reddy, Balaji (Indian Journal of Radiology and Imaging, 2010)
Congenital short bowel syndrome (SBS) is a relatively rare condition as compared to acquired SBS. It is associated with significant mortality and morbidity. Infants usually present with failure to thrive, recurrent vomiting, and diarrhea. It is important to suspect and diagnose this condition promptly, as early initiation of parenteral nutrition or surgery, if necessary, may result in a favorable outcome. We discuss a case of an infant aged 26 days, who presented with failure to thrive, recurrent vomiting, and weight loss. A contrast study of the gastrointestinal tract revealed a short small bowel, with malrotation. The infant was started on parenteral nutrition, but succumbed shortly thereafter to severe disseminated sepsis.
Keywords: Congenital; malabsorption; short bowel syndrome